Dongeng dan Perkembangan Moral Anak - Nur Evira Anggrainy (The Center for Gender and Children Studies, the Institute for Research and Communing Service, State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2021)
This study uses a type of literature review research, by collecting various scientific articles and books and then summing up the results. This study examines the influence of the storytelling method on the moral development of children. The storytelling method is one of the right methods to be used in the learning process. The storytelling method is effective for the moral development of children, especially in early childhood. The results of the literature review revealed that children's moral development focused on tolerance towards friends, being able to distinguish good and bad deeds, fostering empathy such as wanting to be friends with friends and helping friends who were in trouble, listening to the words of parents and teachers, and being obedient to God. The Almighty can increase in early childhood. The storytelling method is also appropriate for children because Indonesia has a variety of folklore that has a moral message so that it not only hones moral development in children but also introduces culture to children from an early age. Abstrak Penelitian ini menggunakan jenis penelitian kajian literatur, dengan cara mengumpulkan berbagai artikel ilmiah dan buku kemudian disimpulkan hasilnya. Penelitian ini mengkaji tentang pengaruh metode mendongeng terhadap perkembangan moral anak. Metode mendongeng merupakan salah satu metode yang tepat untuk dilakukan dalam proses pembelajaran. Metode mendongeng efektif terhadap perkembangan moral anak, khususnya anak usia dini. Hasil telaah literatur yang dilakukan mengungkapkan bahwa perkembangan moral anak yang berfokus pada sikap toleransi terhadap teman, dapat membedakan perbuatan baik dan buruk, menumbuhkan sikap empati seperti mau berteman dengan teman dan menolong teman yang kesulitan, mendengarkan perkataan orang tua dan guru, serta taat kepada Tuhan Yang Maha Esa dapat meningkat pada diri anak usia dini. Metode mendongeng juga tepat dilakukan kepada anak karena Indonesia memiliki beragam cerita rakyat yang memiliki pesan moral sehingga tidak hanya mengasah perkembangan moral pada diri anak, sekaligus memperkenalkan budaya kepada anak sejak dini.